If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + -12b + -12 = 0 Reorder the terms: 60 + -12 + -12b = 0 Combine like terms: 60 + -12 = 48 48 + -12b = 0 Solving 48 + -12b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + -12b = 0 + -48 Combine like terms: 48 + -48 = 0 0 + -12b = 0 + -48 -12b = 0 + -48 Combine like terms: 0 + -48 = -48 -12b = -48 Divide each side by '-12'. b = 4 Simplifying b = 4
| 3y+7y-4y-4y-8=10+4 | | 7/9+(-2/3) | | 10k-3k=7k+84 | | 0=z^2+6 | | 4/5y=40 | | 5x-7x=10x+8 | | -2-4x=10 | | y^2+5=5 | | 12-6p=24+6p | | 50x+5=10x | | 2x+6+42= | | -24+8x=6x-4(x-6) | | 6t(11+5)=0 | | 5-3x=-10 | | 3x+4x+5x-8x+8=12 | | b^2=100 | | -3(1t+5)+(4t+2)=8 | | x=-2(80)+300 | | 4(10x-7)=292 | | 7p-4=1-3p | | 3/5x+8=-12 | | 11m-8=12 | | 3y=800-4(-2y+300) | | 6-4(2x-1)= | | 3x/8=x/2-1 | | 3(2m-4)=18 | | -9b-3=-3[b+2] | | 2(2t-3)=5(2t+3) | | 81=45+5r | | y=4-4(2)+1 | | 21=2x^2+2 | | 2x^2-12y-80=0 |